Autoantibodies to the N-Methyl-D-Aspartate Receptor in Adolescents With Early Onset Psychosis and Healthy Controls - Engen, Kristine; Wortinger, Laura Anne; Jørgensen, Kjetil Nordbø; Lundberg, Mathias; Bohman, Hannes; Smelror, Runar Elle; Myhre, Anne Margrethe; Jacobson, Leslie; Vincent, Angela; Agartz, Ingrid (Frontiers in Psychiatry, 2020)
Background Autoantibodies to the N-methyl-D-aspartate receptor (NMDAR-Abs) in autoimmune encephalitis have been associated with prominent psychiatric symptoms. The aims of the present study are to identify the prevalence of NMDAR-Abs in adolescents with early onset psychosis disorders (EOP) and healthy controls (HC) and examine its clinical significance. Method Plasma samples were acquired from 46 adolescent EOP patients and 69 age- and sex matched HC, and assessed for the presence of immunoglobulin G NMDAR-Abs. All participants underwent psychiatric evaluation, neurological examination and head magnetic resonance imaging. Results NMDAR-Abs were detected in three of 46 (6.5%) EOP patients and in two of 69 (2.9%) HC. One NMDAR-Abs EOP patient presented with unusual psychopathology and minor T1 weighted lesions of vasculopathological origin located bi-frontally and in the basal ganglia, and had a recent diagnosis of a separate autoimmune disease. One NMDAR-Ab HC displayed a T2 weighted FLAIR hyperintensity lesion in the left frontal lobe. The remaining three NMDAR-Ab participants were two EOP patients without neurological or radiological findings, and one HC without any clinical findings. Conclusions We report that a small number of EOP patients and HC have NMDAR-Abs with a similar frequency in both groups. The presence of the antibodies was not associated with any distinctive clinical or radiological features. Detection of the antibodies had no diagnostic implication, and a positive NMDAR antibody test must be carefully interpreted and reviewed within the individual clinical context.